Calibration and Model Risk in the Pricing of Exotic Options Under Pure-Jump Lévy Dynamics - Mboussa Anga, Gael (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015